Controlling as a method for ensuring the financial stability of a family business - B. Dost; Ja. Papula (Науковий вісник Мукачівського державного університету. Серія Економіка, 2025)
The study aimed to analyse the role of controlling as a method for ensuring the financial stability of family businesses and identifying effective methods of its implementation in enterprise management. The study conducted a comprehensive assessment of the impact of controlling the financial stability of family businesses using statistical data, descriptive analysis of the results of an expert survey and analysis of financial statements of real companies (Müller & Söhne GmbH, Bäckerei Schmidt KG, Weber Autoservice) to identify effective management methods and tools. The use of controlling efficiently managed financial flows, increased transparency of operations and improved planning. The analysis demonstrated that family businesses that use a budgeting and financial control system reduce the risks associated with insufficient liquidity and inefficient resource allocation. For instance, after implementing management accounting, Müller & Söhne GmbH reduced costs by 20%, increased net profit from 500,000 EUR to 600,000 EUR, and increased the current ratio from 1.2 to 1.4. At Bäckerei Schmidt KG, profitability increased by 12% over two years and overdue debts decreased from 8% to 4%. At Weber Autoservice GmbH, after the introduction of an early warning system, cash gaps were closed and cash flow from operations increased from 150,000 EUR to 180,000 EUR. Furthermore, the study demonstrated that the successful use of controlling separates personal and corporate finances, improving sustainability. Key tools were analysed, including strategic planning, Balanced Scorecard, key performance indicators and SWOT analysis. Companies that actively use controlling processes demonstrate higher profitability, better solvency and resilience to external risks